Changes of ceruloplasmin and malonic dialdehyde level in patients with cerebral circulatory disorders - Minov, Sergiy; Mironenko, Olena; Parkhomenko, Oleksandr; Zhurahivskiy, Oleksandr (Ukrainian Neurosurgical Journal, 2015)
The purpose. To study role of ceruloplasmin and malonic dialdehyde in pathogenesis of hepatocerebral dystrophy. Changes of malonic dialdehyde concentration in the blood serum indicate the increase of lipid peroxidation intensity and failure of antioxidant protection system. Materials and methods. 30 patients with acute hemorrhagic cerebral circulatory disorders caused by saccular aneurysms rupture with different localization were examined. Patients in the 1st group received combined therapy and Citoflavin, in the 2nd group — received just combined therapy. Results. Ceruloplasmin level increased in all terms of observation in patients who received Cytoflavin and approached to normal as opposed to indicators after combined therapy, indicating energy metabolism disorders. Malonic dialdehyde concentration significantly increased, even in comparison with early stages of the study, indicating a failure of homeostasis compensatory possibilities, which was not observed at Cytoflavin application. Conclusions. Cytoflavin use contributed to normalization of ceruloplasmin level in the early and middle periods of observation with preservation of these indicators in a remote period. Under the influence of Citoflavin level of malonic dialdehyde was close to normal in the medium and remote periods of the study.